Ketepatan Pemberian Makanan Pendamping ASI ( MP ASI ) Oleh Ibu Di Rumah Bersalin Mitra Ananda Palembang Tahun 2018 - Devina Anggrainy Dencik (LPPM STIKes Mitra Adiguna, 2023)
complementary foods (MP-ASI) are foods or drinks that contain nutrients, given to infants or children aged 6-24 months to meet nutritional needs other than breast milk. MP-ASI in the form of solid or liquid food is given in stages according to the age and digestive ability of the baby. At the age of 6-24 months ASI only provides ½ the nutritional needs of infants. And at the age of 12-24 months ASI provides 1/3 of its nutritional needs. So that the MP ASI should be given when the baby is 6 months old (RI Ministry of Health, 2014).By using an analytical survey research design. The population in this study were mothers who had babies 6-12 months in the Mitra Ananda Maternity Hospital in Palembang totaling 52 respondents. The sample in this study was accidental sampling, namely mothers with babies aged 6-12 months totaling 52 respondents in the Ananda Mitra Maternity Hospital in Palembang in 2019.Above of 35 respondents, respondents who gave timely exclusive breastfeeding in giving MP-ASI were 30 respondents (85.7%), who were not on time were 5 respondents (14.3%), and respondents who did not give Exclusive breastfeeding on time for MP-ASI is 17 (100%). From 35 respondents who gave exclusive breastfeeding which was the right way in giving MP-ASI as many as 30 respondents (85.7%) and those who were not right in giving MP-ASI were 5 respondents (14.3%). Respondents who did not give Exclusive ASI the right way in giving MP-ASI as much as 1 (5.9%) and the incorrect way as many as 16 respondents (94.1%). Above of the respondents giving MP-ASI, the number of working mothers with the right type in giving MP-ASI is 16 (72.7%) and the wrong type is 6 respondents (27.3%). There were 15 (50.0%) mothers who did not work in the right type of MP-ASI and those who did not have the right type (15.0%).It is expected that health workers at Mitra Ananda Maternity Hospital can provide information about the importance of providing of giving MP ASI for babies. Keywords : ASI complementary food ( MP ASI )